Intellectual capital and firm performance in the Indonesian non-financial firms - Sofian Sofian; S, Patricia Febrina Dwijayanti; Hendra Wijaya (University of Merdeka Malang, 2020)
This study analyzes the effect of intellectual capital and firm performance in non-financial firms. The firm performance comprises of market performance and financial performance of the firm. This study also breakdown the non-financial firms between three sectors that are the primary sector, manufacturing sector, and service sector. The three sectors are the three main sectors in the economy. This study measures intellectual capital in different ways using the intellectual capital index. The data were analyzed with unbalanced panel data regression and multiple regression. This study found that intellectual capital positively affects market performance and financial performance in non-financial firms. This study also found that intellectual capital positively affects market performance and financial performance in manufacturing and service firms, but in primary sectors, this study found inconclusive results when analyzed and used two different measurements. This study contributes to the firms in non-financial firms about the development of intellectual capital in the knowledge-based economy because intellectual capital is an asset that can create market performance and financial performance.JEL Classification: G32, O34 How to Cite:Sofian, Dwijayanti, S. P. F., Wijaya, H. (2020). Intellectual capital and firm performance in the Indonesian non-financial firms. Jurnal Keuangan dan Perbankan, 24(1), 106-116.DOI: https://doi.org/10.26905/jkdp.v24i1.3574